Diversity of high-molecular-weight glutenin subunits and evaluation of genetic similarities in spring bread wheats from different breeding centers - M. U. Utebayev; N. A. Bome; E. C. Zemtsova; O. O. Kradetskaya; I. V. Chilimova (Труды по прикладной ботанике, генетике и селекции)
Background. Glutenin is a storage protein in wheat seeds, important for the quality of bread prepared from wheat. Studying glutenin polymorphism can help to identify valuable genotypes and promising new breeding lines for further crossings. The aim of this study was to identify subunits of glutenin and determine alleles at the Glu-1 loci in the spring bread wheat germplasm collection. Materials and methods. A panel of 54 Russian and 76 Kazakh bread wheat germplasm accessions from various breeding centers was selected. Gliadin electrophoresis was carried out in a concentrating and separating polyacrylamide gel system following the Laemmli method. Glutenin subunits were identified according to the catalogue produced by Payne and Lawrence. Results and discussion. At the Glu-A1 locus, two alleles, b and  c, were identified, with different frequencies of occurrence among studied wheat accessions. The Glu-A1b allele occurred more frequently than Glu-A1с in the studied germplasm from all breeding centers. Meanwhile, six alleles, а, b, c, d, f and g, were found at the Glu-B1 locus. The most frequently occurring Glu-B1с allele encoded two subunits (7+9). The third homologous gene, Glu-D1, had only two identified alleles, a and d, with various frequencies among the studied wheat accessions. Wheat germplasm of various origin had specific combinations of glutenin subunits, providing different scores of grain quality. For example, the combination of glutenin subunits, 2*, 7+9 and 5+10, provided the highest score (= 9) of grain quality. A single change in the Glu-1 subunit composition, 2*, 7+9 and 2+12, caused a reduction in grain quality (= 7 score); and the combination of Null, 7 and 5+10 was accompanied by the lowest (= 6) grain quality. The analysis showed that two loci, Glu-A1 and Glu-B1, induced significant differences between wheat accessions originated from Tyumen and Chelyabinsk, while the accessions from Chelyabinsk and East Kazakhstan differed significantly at the Glu-A1 and Glu-D1 loci.